Zagadnienie starości w literaturze międzytestamentalnej - Wróbel, Mirosław S. (Vox Patrum, 2011)
In the present article the author describes the problem of an old age in the Jewish apocalyptic literature and in the Qumran texts. Old persons are presented in these texts like sages and teachers. The education given by them for children and grandchildren is based on moral and religious values. They call to observe God’s commandments and to avoid all acts which are against God and other persons. The respect and authority of the old persons described in the texts of intertestamental literature can take in consideration the biblical sources. In the Old Testament the elders of Israel are described as judges who decide about all important aspects of the life in Jewish community.